(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
Sebuku Island is located at the southeastern tip of Kalimantan Island and has geological similarities with the Bobaris-Meratus complex in distribution pattern and stratigraphic sequence. The pattern of straightness of geological structures between the two, both folds and faults, is generally directed from northeast-southwest to northwest-southeast. The previous geological research on Sebuku Island focused on the distribution of ultramafic rocks, which are speculated to contain iron, particularly from laterite soils. This research aims to determine the rock units in the study area to update the geological map of Sebuku Island, especially in the Sei Pinang and Halaban areas. The research method consists of fieldwork, laboratory analyses, and data analyses. The geological fieldwork collected 34 samples from detailed mapping on outcrops, trenching, and drilling. Geological structure observations were carried out on fresh outcrops and measured 57 structural geological elements from 6 locations. Petrographic analysis of 34 samples was carried out with the aim of determining rock type and mineralogical composition. Stereographic analysis of geological structure measurement data was used to define the general direction and type of geological structures in the investigated outcrops. The geological map is constructed on the basic topographic map in the scale 1:50,000 using MapInfo Pro v17.0.5. Based on petrographic observations and detailed field observations, especially in North Damar, from surface outcrops and drill core observations from Madang, the following results are revealed. In the geology of North Damar, in particular, and Sebuku Island, in general, the lithology can be described as an ultramafic rock unit (lherzolite, harzburgite, and dunite), pyroclastic rock unit (crystallo-lithoclastic tuff and crystalloclastic tuff), limestone unit, dike rock unit (microgabbro and diorite), sandstone unit, and alluvial deposit. Almost 60% of Sebuku Island outcrops belong to the ultramafic rock units, which are tectonically covered by crystalline lithic tuff and crystalline tuff and volcaniclastic rock units with interbedded limestone, unconformably covered by sandstone units, alluvial deposits, and swamp deposits. Microgabbro and diorite were observed from the drill core and were not exposed to the surface. Hydrothermal mineralization is indicated by quartz veins cross-cutting the pyroclastic rock group observed in drill cores. This research shows a more detailed geological description of the study area compared to previous research and regional geological map.